Improving Islamic Education Learning Outcomes Using Group Discussion Methods for Students at State Elementary School 25 Sungai Nyalo - Meliati (Jurnal Profesi Guru Indonesia, 2024)
This study aims to improve Islamic education learning in Islamic religious education learning by using group discussion method. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data of this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the group discussion learning method can improve the group discussion method on Asmaul Husna in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 46.78%, the first cycle 53.81% and in the second cycle increased to 51.59%. Thus, the use of group discussion method can be used as an alternative to improve student learning outcomes in Islamic religious education learning.